Identifying key sectors using regional input-output model at sub-national level - Sunggoan Choi; Haemyoung Ji; Xiaoyun Zhao (European Regional Science Association (ERSA), 2014)
Since key sectors have high backward and forward linkages with rest of the economy, investment in these sectors is expected to maximize the economic growth, which is extensively meaningful in undeveloped or developing countries with limited resources. Besides, it is considerably necessary and helpful to identify key sectors for analyzing the long-term structural change and economic development strategic policy, both at national and regional level. However, identification of the key sectors is somehow difficult to carry out in practice at regional level due to the absence of regional data at hand. In this study, we employ the traditional backward and forward linkages as indicators to identify the key sectors for sub-national regions, where the input-output (IO) tables are unavailable, along with non-survey techniques. The regional IO tables are produced from adjusting national IO tables with several non-survey techniques. To capture the performance of non-survey techniques on recognizing key sectors, then, the estimated regional backward/forward linkages are computed, which are represented by the output multipliers, and compared with the survey based benchmarks through the rank correlation coefficients. A big value of correlation indicates a high capability of the non-survey techniques on the identification of regional key sectors. At last, empirical study is given with Korean 2005 national and regional IO tables.
Keywords: 330; Regional Input-Output model; Location quotients; Non-survey techniques; Key sectors; Linkage effect